2020
DOI: 10.3390/jcm9030882
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Non-Invasive Brain Stimulation Techniques to Reduce Violence Proneness by Interfering in Anger and Irritability

Abstract: The field of neurocriminology has proposed several treatments (e.g., pharmacological, brain surgery, androgen-deprivation therapy, neurofeedback) to reduce violence proneness, but unfortunately, their effectiveness has been limited due to their side-effects. Therefore, it is necessary to explore alternative techniques to improve patients’ behavioural regulation with minimal undesirable effects. In this regard, non-invasive brain stimulation techniques, which are based on applying changing magnetic fields or el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Air pollution is associated with behavioral changes because because it causes people to spend less time in the open and lead a more sedentary lifestyle, which can cause psychological distress and social isolation ( 66 , 67 ). The main negative effects of air pollution on the nervous system are more irritability, aggression, anger, and intolerance ( 68 , 69 ). Figure 3 shows sources of emission of toxic air pollutants in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Air pollution is associated with behavioral changes because because it causes people to spend less time in the open and lead a more sedentary lifestyle, which can cause psychological distress and social isolation ( 66 , 67 ). The main negative effects of air pollution on the nervous system are more irritability, aggression, anger, and intolerance ( 68 , 69 ). Figure 3 shows sources of emission of toxic air pollutants in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…As it has in the present study, investigating higher brain functions such as mental imagery might expand our physiological and pathological understanding of psychiatric disorders and facilitate the search for their biomarkers. Furthermore, neural decoding might help treat psychiatric disorders by application of its detailed results to neuromodulation methods such as neurofeedback (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and transcranial stimulation (88,89).…”
Section: Imagery-related Neural Oscillationsmentioning
confidence: 99%
“…In recent years, neural decoding research has progressed along with the expansion of machine learning (ML). Neural decoding has also been applied for interpreting mental states (1,2) and for treating various psychiatric disorders with neurofeedback (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). With the development of deep learning, decoding performance improvement is accelerating.…”
Section: Introductionmentioning
confidence: 99%
“…It might even be possible to go further and assess if there is an intrinsic resting-state activity relevant to understanding why certain individuals tend to react with violence. In fact, two recent systematic reviews concluded that this type of analysis could be used as an indicator or trait for proneness to violence 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the violence linked to this imbalance could be attributed to high emotional content and impulsivity 15 . This model suggests that prefrontal regions (control system) are unable to regulate limbic irritability, which facilitates behavioral instability and violence under uncertain circumstances 12 , 13 , 15 . However, it is important to understand whether this imbalance is also applicable during resting periods or only during emotional processing processes.…”
Section: Introductionmentioning
confidence: 99%